Biological fitness of Trichoderma atroviride during long-term storage, after production in different culture conditions. Issue 1 (2nd January 2016) - Daryaei, Amir; Jones, E. Eirian; Glare, Travis R.; Falloon, Richard E.
ABSTRACT: Identification of the production and storage factors that affect conidium germination and bioactivity (fitness) will assist the success of biological control agents. Effects of culturing conditions on conidium fitness of Trichoderma atroviride LU132 were examined in different storage conditions over time. Abiotic factors (temperature, nutrients, water activity and pH) during production were studied. Conidia from the culturing regimes which resulted in greatest and least bioactivity against Rhizoctonia solani in dual culture were selected to assess effects of storage conditions on conidium fitness. Fitness of the test conidia was examined after storage at 30°C and at 0% or 50% relative humidity (RH) over 6 months. Fitness declined over time, and the decline was greater for 50% RH than 0% RH, probably through reduced metabolic activity of conidia during long-term storage. Stored conidia were probably affected by dehydration, temperature and other factors such as oxidation, before and during storage, and also by rehydration after storage. The greatest number of conidia and germination percentage resulted from production at 25°C, but greatest bioactivity resulted from those produced at 30°C. No significant effects on bioactivity were detected between the conidium production treatments C : N 5 : 1 and C : N 160 : 1, indicating that C : N ratio in culture medium is not important for conidium survival of T. atroviride .